Pengaruh Pelatihan Kedisiplinan dalam Meningkatkan Disiplin Belajar Siswa di Sekolah Menengah Pertama - Ismira Dewi; Asmadi Alsa (Jurnal Psikologi Integratif, 2016)
Discipline is a compulsary subject in school because without the discipline, the process of teaching-learning will not be optimal. Student discipline can be achieved by increasing students' learning discipline in class. Discipline Training is expected to increase the discipline of students in the learning process in class. This research using untreated control group design with dependent pre-test and post-test sample method. Data taken using a scale of students' learning discipline.Participantsofthis study are 30 students in junior high school, aged 13 - 15 years. 15 subjects were the control group and 15 subjects were the experimental group. Data analysis using anava mixed design. Results showed increased significant in the experimental group, before and after training given. The presence of interaction indicates that there is changes in pre to post scores in both groups (experimental - control) was significantly different, F = 4,756(p < 0,05). Based on the analysis results it can be concluded that student disciplinary training can increase students' learning discipline in the classroom.